THE MEANING OF LEARNING FOR STUDENTS IN RURAL AREAS: A QUALITATIVE NARRATIVE APPROACH - Rahmawati, Alfi Mufida; Nisa', Liza Choirun; Ananto, Gigih Dwi (EDUCATUM: Scientific Journal of Education, 2025)
This study aims to explore the meaning of learning as experienced and constructed by students living in rural areas through a qualitative narrative approach. Learning is not merely an academic process, but a lived experience shaped by social, cultural, and economic contexts. Despite the growing attention to educational issues in rural settings, limited research has focused on how students themselves interpret the meaning of learning from their own perspectives. This study addresses this gap by foregrounding students’ narratives as the primary source of understanding. A qualitative narrative inquiry design was employed to capture students’ lived experiences through in-depth narrative interviews and contextual observations. The research was conducted in schools located in rural areas characterized by limited educational resources, restricted access to technology, and constrained economic opportunities. Participants were selected purposively to represent diverse rural backgrounds. Data were analyzed using narrative-thematic analysis to identify recurring meanings embedded in students’ stories. The findings reveal that learning is constructed as a multidimensional experience. For rural students, learning is perceived as a pathway to socio-economic mobility, a moral responsibility toward family and community, a site of tension between aspiration and structural limitation, and a process of identity formation. Students associate learning with hopes of improving their families’ economic conditions, fulfilling parental expectations, and building a better future. At the same time, they face significant challenges, such as limited facilities and competing domestic responsibilities, which shape their learning experiences and require resilience and adaptation. This study contributes to educational research by providing a contextual and humanistic understanding of learning in rural settings. Practically, the findings suggest that educational practices and policies should be more sensitive to students’ lived realities and local contexts, positioning learning not only as curriculum delivery but as a meaningful process of social transformation.